The Influence of CSR, Profitability and Leverage on Company Value with Company Size as a Moderator - Zico Is Mirza Wijaya; Suharsono, Riyanto Setiawan; Ibna Kamelia Fiel Afroh (Finance : International Journal of Management Finance, 2024)
This study aims to examine the influence of Corporate Social Responsibility (CSR) disclosure, profitability, and leverage on firm value, with company size as a moderating variable. The analysis employed multiple linear regression and moderated regression analysis (MRA) on manufacturing companies listed on the Indonesia  Stock Exchange. The findings indicate that CSR profitability, and leverage positively impact firm value, while company size significantly moderates these relationships. These results suggest that large firm with CSR disclosures and sound financial performance tend to have higher firm value. The implications provide insights for management and stakeholders regarding the importance of CSR strategies and financial management in enhancing firm value, especially for larger companies. Empirically, this reseacrh contributes to the literature by highlighting the role of company size as moderating variable in the relationship between financial and non financial variables and firm value.